The Mediatization of “SARA” Conflict in Indonesian Online Media - Eni Maryani; Detta Rahmawan; Irma Garnesia (Asosiasi Pendidikan Tinggi Ilmu Komunikasi (ASPIKOM), 2019)
This study aims to analyses the news on